Broadly neutralizing antibodies for HIV-1 prevention and therapy. (January 2021) - Julg, Boris; Barouch, Dan
Abstract: Despite immense progress in our ability to prevent and treat HIV-1 infection, HIV-1 remains an incurable disease and a highly efficacious HIV-1 vaccine is not yet available. Additional tools to prevent and treat HIV-1 are therefore necessary. The identification of potent and broadly neutralizing antibodies (bNAbs) against HIV-1 has revolutionized the field and may prove clinically useful. Significant advances have been made in identifying broader and more potent antibodies, characterizing antibodies in preclinical animal models, engineering antibodies to extend half-life and expand breadth and functionality, and evaluating the efficacy of single bNAbs and bNAb combinations in people with and without HIV-1. Here, we review recent progress in developing bNAbs for the prevention and treatment of HIV-1.